Idecabtagene vicleucel is well tolerated and effective in relapsed/refractory myeloma patients with prior allogeneic stem cell transplantation - John, Lukas; Sauer, Sandra; Hegenbart, Ute; Dreger, Peter; Hundemer, Michael; Müller-Tidow, Carsten; Schmitt, Anita; Schmitt, Michael; Raab, Marc-Steffen; Schönland, Stefan (Transplantation and cellular therapy, 2023)
BCMA-specific chimeric-antigen receptor (CAR-) T cell therapy has led to high response rates and durable remissions in patients with relapsed refractory multiple myeloma. However, little data are available for patients after prior allogeneic stem cell transplantation (allo-SCT) in whom T cells are chimeric. In this study, we aimed to assess the safety and efficacy of patient-derived donor CAR-T therapy in myeloma patients with prior allo-SCT, particularly with regard to graft-versus-host disease (GVHD). We report a comprehensive clinical analysis of 3 patients who had previously undergone allo-SCT for high-risk myeloma and were treated with idecabtagene vicleucel (ide-cel) at our institution. Ide-cel was well tolerated, with no clinically relevant immune effector cell-associated neurotoxicity syndrome or cytokine release syndrome observed in any patient. Importantly, no new GVHD was observed, even though all patients had a history of GVHD. All patients responded to treatment with at least a very good partial remission. Two patients relapsed within 6 months, and 1 patient was still in stringent complete remission at the time of this report. Our findings demonstrate that treatment with ide-cel is feasible, very well tolerated, and effective in patients with relapsed/refractory multiple myeloma after prior allo-SCT.
Online verfügbar 20 June 2023, Version des Artikels 11 October 2023
Gesehen am 17.01.2024